Development of polycaprolactone based controlled release fertilizer for mung bean crop - Pakalapati, Harshini (2019)
Pulses are a major source of protein, rich in vital elements supplying a substantial part of the calorie and nutrients. To ensure wholesome gram cultivation, nutrients are supplied to the soil for plant uptake. However, excessive release of nutrients leads to several environmental issues like depletion of soil quality, biological imbalance in water bodies and climate change. Thus, proper nutrient management is essential for a healthy crop in terms of both quality and quantity. This can be achieved through control release of nutrients by encapsulating the fertilizers within polymers. Therefore, this work focuses on the supply of essential nutrients to mung bean crop encapsulated within biodegradable polymers. Further, the effect of biochar dozed along with encapsulated system is investigated. In this current research, initially the pot trials were carried out formulating with different levels of biochar and nutrients, results showed improved growth characteristics and crop yield when biochar of 20kg/ha and NPK of 30kg/ha was applied. Later, polycaprolactone (PCL) was synthesised using Candida antarctica lipase B (CALB) as catalyst, using design of experiments (DOE). Optimised parameters are found to be - time - 1hr, RPM - 500 rpm, temperature - 75°C and monomer/solvent ratio to 1:2, therefore successfully implementing D optimal design from DOE for optimisation of process parameters for PCL synthesis. Further, PCL was targeted to develop controlled release fertilizer (CRF) due to its biodegradability and non- toxic nature. Subsequently, two different techniques have been used to prepare control release fertilizers – solvent casting and blending techniques. When analysed with nutrient release properties and their effect on mung bean growth, blending technique is considered to be better. Since blending is easy to handle involving no solvent and potential scalable technique to prepare PCL based CRF blends. Out of the three-concentration used, 25% (i.e. blend with PCL/starch ratio is 5:1) was recorded to be less porous with significant controlled release of fertilizers. Moreover, in final plant trials, PCL blended CRF had a notable effect on the growth and yield of the mung bean with 39% more yield (i.e. total seed weight) compared with non- PCL blended fertilizer (normal NPK fertilizer). Thus, PCL based controlled release fertilizers are developed which helps to maintain a sustainable cultivation system.